Nintedanib in combination with pemetrexed and cisplatin for chemotherapy-naive patients with advanced malignant pleural mesothelioma (LUME-Meso): a double-blind, randomised, placebo-controlled phase 3 trial. Issue 7 (July 2019) - Scagliotti, Giorgio V; Gaafar, Rabab; Nowak, Anna K; Nakano, Takashi; van Meerbeeck, Jan; Popat, Sanjay; Vogelzang, Nicholas J; Grosso, Federica; Aboelhassan, Rasha; Jakopovic, Marko; Ceresoli, Giovanni L; Taylor, Paul; et al.
Summary: Background: Nintedanib targets VEGF receptors 1–3, PDGF receptors α and β, FGF receptors 1–3, and Src and Abl kinases, which are all implicated in malignant pleural mesothelioma pathogenesis. Here, we report the final results of the phase 3 part of the LUME-Meso trial, which aimed to investigate the efficacy and safety of pemetrexed plus cisplatin combined with nintedanib or placebo in unresectable malignant pleural mesothelioma. Methods: This double-blind, randomised, placebo-controlled phase 3 trial was done at 120 academic medical centres and community clinics in 27 countries across the world. Chemotherapy-naive adults (aged ≥18 years) with unresectable epithelioid malignant pleural mesothelioma and ECOG performance status 0–1 were randomly assigned 1:1 via an independently verified random number-generating system to receive up to six 21-day cycles of pemetrexed (500 mg/m 2 ) plus cisplatin (75 mg/m 2 ) on day 1, then nintedanib (200 mg twice daily) or matched placebo on days 2–21. Patients without disease progression after six cycles received nintedanib or placebo maintenance on days 1–21 of each cycle. The primary endpoint was progression-free survival (investigator-assessed according to mRECIST) in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of their assigned study drug. This study is registered withClinicalTrials.gov, numberNCT01907100 . Findings: Between April 14, 2016, and Jan 5, 2018, 541 patients were screened and 458 were randomly assigned to either the nintedanib group (n=229) or the placebo group (n=229). Median treatment duration was 5·3 months (IQR 2·8–7·3) in the nintedanib group and 5·1 months (2·7–7·8) in the placebo group. After 250 events, progression-free survival was not different between the nintedanib group (median 6·8 months [95% CI 6·1–7·0]) and the placebo group (7·0 months [6·7–7·2]; HR 1·01 [95% CI 0·79–1·30], p=0·91). The most frequently reported grade 3 or worse adverse event in both treatment groups was neutropenia (73 [32%] in the nintedanib group vs 54 [24%] in the placebo group). Serious adverse events were reported in 99 (44%) patients in the nintedanib group and 89 (39%) patients in the placebo group. The only serious adverse event occurring in at least 5% of patients in either group was pulmonary embolism (13 [6%] vs seven [3%]). Interpretation: The primary progression-free survival endpoint of the phase 3 part of LUME-Meso was not met and phase 2 findings were not confirmed. No unexpected safety findings were reported. Funding: Boehringer Ingelheim.